ANALYSIS OF THE URGENCY OF ISLAMIC EDUCATION MANAGEMENT GLOBALIZATION ERA - Ali Munirom (Universitas Labuhanbatu, 2023)
Advances in science and technology are currently growing in supporting education in Indonesia. Educators and students must be able to balance so as not to be left behind by other regions outside Indonesia. The purpose of conducting this research is to find the urgency of management of Islamic education in the era of globalization. This research is a type of library research. Library research is research that is carried out using literature in the form of books, notes and research reports from previous studies. The data that the researchers will use in this study are obtained from books, articles and websites related to this research. The approach used in this research is a qualitative approach. The qualitative approach is a descriptive research and tends to use analysis. Process and meaning are highlighted in qualitative research. The results of the study above found that the urgency of education management has an important role starting from planning, organizing, directing to supervising in creating an ideal education in the era of globalization. Islamic education management is the implementation of Islamic values that are instilled in carrying out activities carried out by Muslims both in economic, social and educational activities. The existence of an Islamic sharia basis can be a person's control in carrying out life in this era of globalization where the rationality of the human mind is prioritized so that if the sharia values are not instilled in oneself they can be lost.Keywords: Management of Islamic Education, Globalization Era AbstrakKemajuan ilmu pengetahuan dan teknologi saat ini semakin berkembang dalam menyokong pendidikan yang ada di Indonesia. Pendidik dan peserta didik harus mampu mengimbangi agar tidak tertinggal dengan wilayah lain diluar Indonesia. Tujuan dilakukannya penelitian ini adalah untuk menemukan urgensi manajemen pendidikan Islam era globalisasi. Penelitian yang dilakukan ini merupakan jenis penelitian library research. Library research merupakan adalah penelitian yang dilaksanakan dengan menggunakan literatur (kepustakaan) baik berupa buku, catatan maupun laporan hasil penelitian dari penelitian terdahulu. Data yang akan peneliti gunakan dalam penelitian ini peneliti peroleh dari buku-buku, artikel dan website yang berkaitan dengan penelitian ini. Pendekatan yang digunakan dalam riset ini adalah pendekatan kualitatif. Pendekatan kualitatif merupakan penelitian yang bersifat deskriptif dan cenderung menggunakan analisis. Proses dan makna lebih ditonjolkan dalam penelitian kualitatif. Hasil penelitian menemukan bahwa urgensi manajemen pendidikan islam ditengah-tengah era globalisasi memiliki perang penting mulai dari perencanaan, pengorganisasian, pengarahan hingga pengawasan. Manajemen pendidikan islam adalah implementasi dari nilai-nilai islam yang ditanamkan dalam menjalankan kegiatan yang dilakukan oleh muslim baik dalam kegiatan ekonomi, sosial maupun pendidikan. Adanya landasan syariat Islam dapat menjadi kontrol seseorang dalam menjalankan kehidupan di era globalisasi ini dimana rasionalitas fikiran manusia lebih diutamakan sehingga nilai-nilai syariat jika tidak ditanamkan dalam diri dapat saja hilang.Kata Kunci: Manajemen Pendidikan Islam, Era Globalisasi